The Carbon Chain in Carbon Dioxide Industrial Utilization Technologies A Case Study - Wawrzyńczak, Dariusz; Majchrzak-Kucęba, Izabela; Pevida, Covadonga; Bonura, Giuseppe; Nogueira, Rita; De Falco, Marcello (Taylor & Francis, 2023)
A shift towards implementation of renewable energy has disadvantages, such as power availability, storage capacity, and accompanying costs, and therefore the potential of clean fossil fuel technologies to ensure the stability of electricity generation needs to be reconsidered until these challenges will be overcome. These clean technologies can help prevent the greenhouse effect and, at the same time, guarantee energy security, as coal is a widespread, price-stable raw material that is available in large quantities. This book focuses on the carbon chain, starting from the formation of CO2, through its capture, possible cleaning, to the production of useful products such as dimethylether, methanol, and carbonated cement prefabricates. The comprehensive case study presents the research results of an international team established within the "CCS-CCU technology for carbon footprint reduction using bio-adsorbents" (BIOCO2) project.